Feeling (Un)safe in Prison: A Comparative Analysis of England & Wales and Norway - Martens, Sophie (The British journal of criminology, 2025)
While there is abundant literature on prison violence, much less has been written about how safety is perceived and conceived in prison. Even less is known about how these feelings of safety and their respective predictors may vary between prison systems. This study illustrates what predicts feelings of safety and how prisoners define and experience safety in two jurisdictions, Norway and England & Wales. The research employs a mixed-methods approach, using data from surveys (N = 984) and interviews (N = 199) from a major comparative penological project. It finds that while prisoners in Norway generally reported feeling safer than prisoners in England & Wales, the quantitative predictors of safety did not vary by jurisdiction. From a qualitative perspective, however, it was observed that prisoners in England & Wales held a more limited definition of safety (bounded safety) in which they accepted a constant need for vigilance, whereas prisoners in Norway showed more trust in their environment. This finding suggests that feelings of safety in prison may be (at least partly) context-dependent, which raises important questions regarding the much-debated ‘safety paradox’ in prison, and forms a relevant insight for future comparative work.